A supramolecular approach to improve the gene transfection efficacy of dendrimers1. Issue 47 (14th June 2015) - Shao, Naimin; Dai, Tianjiao; Liu, Yan; Cheng, Yiyun
<x xml:space="preserve">Abstract</x> Cyanuric acid is able to form complementary hydrogen bonds with melamine.